Investigation of factors potentially influencing calcitonin levels in the screening and follow-up for medullary thyroid carcinoma: a cautionary note - Guesgen, Christoph (BioMed Central, 2013)
BACKGROUND: The malignant transformation of thyroid C cells is associated with an increase in human calcitonin (hCT), which can thus be helpful in the early diagnosis of medullary thyroid carcinoma (MTC). For this reason, hCT levels should be determined in all patients with nodular goitre. Hashimoto’s thyroiditis, nodular goitre and proton pump inhibitor (PPI) therapy are factors reported to influence basal serum hCT concentrations. The diagnostic role of mildly to moderately increased hCT levels is thus a matter of debate. In this study, we attempt to clarify the role of the aforementioned factors. METHODS: From 2008 to 2009, we collected data from 493 patients who were divided into five groups. We assessed whether there were significant differences in hCT levels between patients with Hashimoto’s thyroiditis, patients with nodular goitre, patients with PPI therapy, and healthy control subjects. In addition, we investigated whether a delayed analysis of blood samples has an effect on serum hCT concentrations. RESULTS: Immunoradiometric assays (Calcitonin IRMA magnum, MEDIPAN) revealed that the time of analysis did not play a role when low levels were measured. Delayed analysis, however, carried the risk of false low results when serum hCT concentrations were elevated. Men had significantly higher serum hCT levels than women. The serum hCT concentrations of patients with Hashimoto’s thyroiditis and nodular goitre were not significantly different from those of control subjects. Likewise, PPI therapy did not lead to a significant increase in serum hCT concentrations regardless of the presence or absence of nodular goitre. CONCLUSIONS: Increases in serum hCT levels are not necessarily attributable to Hashimoto’s thyroiditis, nodular goitre or the regular use of PPIs and always require further diagnostic attention.